Pertumbuhan Populasi Mikroalga Spirulina platensis (Geitler) Pada Konsenterasi Logam Berat Tembaga (Cu) - Danu Maulana (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2014)
One of heavy metal which is a source of pollution and need to be minimized its concentration on water is heavy metal cooper (Cu). In humans, chronic Cu poisoned lead to liver cirrhosis, brain damage, kidney damage and deposition of Cu in the cornea of the eye. The concentration of heavy metals in water can be remediate using microalgae, related to its biosorption potential some research on heavy metal binding ions to microalgae has been done, species Chlorella vulgaris, Phormidium sp., Dunaliella tertiolecta, Nostoc sp., Euglena gracilis has a high tolerance to heavy metal ions. The purpose of this study is to examine the effect of heavy metals Cu on populations of S. platensis and determine a decrease in the concentration of heavy metals Cu in cultures of S. platensis, compared to the long presentation time. Research using 4 treatment concentrations of Cu ie 0; 1; 3; and 5 mg / l with 3 replications respectively. The results showed the concentration of Cu treatment affects the population growth of S. platensis. S. platensis able to decrease the concentration of Cu in the culture medium. The larger the population of S. platensis, the greater absorption of Cu by the cell. The decrease percentage in Cu in the medium is directly proportional to the exposure time needed. S. platensis can be used as fikoremediator of heavy metal Cu at a concentration 1 mg / l of Cu.Keywords: Spirulina platensis, Fikoremediation, Biosorption, Heavy metals, Cu.